THE ANXIETIES OF TIME IN THE SOCIAL LYRICS OF KYAZIM MECHIEV - BITTIROVA, T.Sh (Kavkazologiya, 2021)
This article aims to determine the place of the topic of social justice in the work of the classic of Karachai-Balkarian literature Kyazim Mechiev and the forms of its artistic embodiment. The scientific novelty lies in the fact that for the first time the poet's social lyrics are viewed in a broad historical context, in relation to the chronotope. The results obtained showed the scale of the poet's thinking, his sensitivity to historical and political transformations in the life of highland society. The work establishes how the events of the early twentieth century are refracted through the author's worldview and what place the theme of social protest occupies in the poetic heritage of the classic of Karachai-Balkarian literature K.B. Mechiev. Analyzed the poems of K. Mechiev, dedicated to the pre-revolutionary and revolutionary events, the civil war, their accordance to historical realities. The article reveals the depth and scale of reflection of the challenges of the time in the poet's work, his pain, despair and hope.